A first course in fuzzy logic - Nguyen, Hung T. 1944-; Walker, E. (Elbert) 1930- (Chapman & Hall/CRC, 2006)
'A First Course in Fuzzy Logic' offers a solid introduction to fuzzy set theory & its applications, & emphasises the mathematical basis of fuzzy logic. Exercises at the end of each chapter serve to deepen the reader's understanding of the topic